Transcriptome analysis of Paris polyphylla var. yunnanensis illuminates the biosynthesis and accumulation of steroidal saponins in rhizomes and leaves. (October 2020) - Gao, Xiaoyang; Zhang, Xuan; Chen, Wen; Li, Jing; Yang, Wenjing; Zhang, Xingwang; Li, Shengying; Liu, Changning
Abstract: Paris polyphylla var. yunnanensis can synthesize Paris saponins with multiple effective therapies, and its rhizome has become an indispensable ingredient in many patented drugs. However, how Paris saponin content changes in tissues at different stages and the molecular mechanisms underlying the production and accumulation of the bioactive compounds are unclear. This study aimed to uncover the mechanisms underlying the biosynthesis and accumulation by integrating transcriptome sequencing and phytochemical investigation of the leaves and rhizomes at different growth stages. Paris saponin content in leaves was lower during the fruiting stage than the vegetative stage, whereas the content in rhizomes increased during the fruiting stage. The candidate genes related to Paris saponin biosynthesis were determined by transcriptome analyses. Most biosynthetic genes were found to be abundantly expressed in the leaves during the vegetative stage in the light of expression profiles and functional enrichment results. The expression patterns of the differentially expressed genes related to the biosynthesis were positively correlated with the accumulation of saponins in tissues. These findings suggest that both leaves and rhizomes are capable of biosynthesizing Paris saponins, and that aerial plant parts can be used to extract them. The different patterns of biosynthesis and accumulation in the leaves and rhizomes were also determined here. This study will help improve our understanding of the mechanisms underlying the biosynthesis and accumulation of Paris saponins, and aid in the comprehensive development and utilization of this medicinal plant. Graphical abstract: Image 1 Highlights: Mechanisms underlying the biosynthesis and accumulation of Paris saponins are explored by integrating RNA-Seq and HPLC. The change tendency of Paris saponins in the leaves across growth stages is opposite to that in the rhizomes. Most biosynthetic genes were abundantly expressed in the leaves and leaves can be used to extract the compounds. The expression patterns of the biosynthetic genes were positively correlated with accumulation patterns of Paris saponin.